PENGAYAAN BELAJAR DENGAN PERSONAL AI PEER DALAM KULIAH TEKNIK ELEKTRO [ENRICHING LEARNING WITH PERSONAL AI PEERS IN ELECTRICAL ENGINEERING LECTURES] - Dr.-Ing. Ihan Martoyo, S.T., M.Sc., M.T.S. (Universitas Pelita Harapan, 2026)
A disruptive potential of AI in enriching learning experiences is to provide a personalized learning pathway by functioning as a personal peer for learners. However, this requires a learning activity plan that goes beyond just submitting essays for final grading, which is automated easily by AI and can be detrimental for the learning processes. This article describes the experiences of using AI as part of a lecture activity in the Electrical Engineering Department, Universitas Pelita Harapan as a personalized peer for the students’ understanding and critical thinking in the Data Science and Tech-Business classes. As part of the assignments, after summarizing a lecture in short paragraphs, the students were engaged in a dialog with AI with their own questions, then posted and analyzed the results in the Learning Management System (LMS) forum to be debated by the other students. The grades were given by the quality of the interactions or by follow-up debate sessions. Some positive correlations have been found between the student accesses in the LMS and the class scores/grades (r = 0.49 & r = 0.39). The qualitative comments of the courses have also indicated some positive and constructive learning experiences, despite the rather high difficulty levels of the courses. The benefits, drawbacks and dilemmas of such a lesson planning strategy are also discussed in this paper. Abstrak Bahasa Indonesia Potensi disruptif AI dalam memperkaya pengalaman belajar adalah dengan menyediakan jalur pembelajaran sesuai kebutuhan personal dengan berfungsi sebagai peer pribadi bagi peserta didik. Namun, ini memerlukan rencana aktivitas pembelajaran yang lebih dari sekadar menyerahkan esai untuk penilaian akhir, yang diotomatisasi dengan mudah oleh AI dan dapat merugikan proses pembelajaran. Makalah ini menjelaskan pengalaman penggunaan AI sebagai bagian dari aktivitas perkuliahan di program studi Teknik Elektro, Universitas Pelita Harapan sebagai alat untuk meningkatkan pemahaman dan pemikiran kritis mahasiswa dalam kelas Sains Data dan Teknologi-Bisnis. Sebagai bagian dari tugas, setelah meringkas kuliah dalam paragraf pendek, mahasiswa harus terlibat dalam dialog dengan AI dengan pertanyaan mereka sendiri, dan memposting serta menganalisis hasilnya di forum Learning Management System (LMS) agar dapat direspons oleh mahasiswa lain. Nilai akan diberikan berdasarkan kualitas interaksi atau sesi debat lanjutan. Korelasi positif ditemukan antara akses mahasiswa di LMS dan score/nilai kelas (r = 0,49 & r = 0,39). Komentar kualitatif terhadap kelas-kelas tersebut juga menunjukkan pengalaman belajar yang positif dan konstruktif, meskipun tingkat kesulitan cukup tinggi. Manfaat, kerugian dan dilema dari strategi rencana pembelajaran seperti itu dibahas di artikel ini.